Pengaruh Locus of Control terhadap Kematangan Karir yang Dimediasi oleh Self-Efficacy pada Mahasiswa - Djunaedi, Nibrasabiyya; Juwitaningrum, Ita; Ihsan, Helli (JURNAL PSIKOLOGI INSIGHT, 2022)
Abstract  This study aims to determine the locus of control effect on career maturity mediated by self-efficacy in students. This study uses a quantitative approach with the number of respondents as many as 400 students aged 18-23 years who are studying at the Indonesian Education University. The sampling technique used is quota sampling which is determined based on the population. This study uses three instruments, namely Rotter's Locus of Control Scale for locus of control, General Self-efficacy (GSE) to measure self-efficacy, and Career Maturity Inventory-Form C (CMI-C) to measure career maturity. The data analysis technique in this study uses the causal step method and the product of  coefficient analysis method. Research results showed that locus of control influences career maturity through self-efficacy as a mediating variable for undergraduates. It proves the hypothesis in this research that self-efficacy mediates the relationship between locus of control on career maturity.Keywords: career maturity, locus of control, mediation research, self-efficacy, undergraduatesAbstrak Penelitian ini bertujuan untuk mengetahui apakah terdapat pengaruh locus of control terhadap kematangan karir yang dimediasi oleh self-efficacy pada mahasiswa. Penelitian ini menggunakan pendekatan kuantitatif dengan jumlah responden sebanyak 400 mahasiswa berusia 18-23 tahun yang menempuh pendidikan di Universitas Pendidikan Indonesia. Penelitian ini menggunakan tiga instrumen yaitu Rotter’s Locus of Control Scale untuk locus of control, General Self-efficacy (GSE) untuk mengukur self-efficacy, dan Career Maturity Inventory-Form C (CMI-C) untuk mengukur kematangan karir. Teknik analisis data pada penelitian ini menggunakan metode kausal step dan metode analisis product of coefficient. Hasil penelitian menunjukkan bahwa locus of control berpengaruh terhadap kematangan karir melalui self-efficacy sebagai variabel mediasi pada mahasiswa. Hal ini membuktikan hipotesis dalam penelitian ini bahwa self-efficacy memediasi hubungan antara locus of control terhadap kematangan karir.Kata kunci: kematangan karir, locus of control, mahasiswa, penelitian mediasi, self-efficacy.